Legal Protection towards the Beneficiaries of PT Asuransi Jiwasraya due to Payment Defaults of the Jiwasraya Savings Plan: A Critical Review - Rizky Amalia Solichin (Universitas Negeri Semarang, 2021)
The failure of Jiwasraya's claim settlements was since it was not a part of their insurance product and it did not comply with UU No. 40 Tahun 2014. The creation of this research article is to comprehend the unlawful effect of such failure and places responsibility on parties deemed responsible for the losses caused. This research is normative-law research-based, given the evidence of the mismanagement of PT. Asuransi Jiwasraya did not comply with the law and how their board of management disobeyed good governance. Theoretically, PT. Asuransi Jiwasraya bears responsibility, as mentioned in their contractual liability that holds the company responsible. As such is the right of the owner of the insurance policy bought from PT. Asuransi Jiwasraya. As PT. Asuransi Jiwasraya is a state-owned enterprise - the Indonesian government is also partly responsible for its failure. With that in mind, the government has mandated restructuring the Financial Services Authority (OJK) and increasing financial surveillance on PT. Asuransi Jiwasraya, putting the insurance company on a short leash.